COVID-19 Outbreaks in Settings With Precarious Housing Conditions in Germany: Challenges and Lessons Learned - Zimmermann, Ruth; Sarma, Navina; Thieme-Thörel, Doris; Alpers, Katharina; Artelt, Tanja; Azouagh, Karima; Bremer, Viviane; Broistedt, Petra; Eckmanns, Tim; Feltgen, Nicolas; Huska, Matthew; Kröger, Stefan; et al. (Frontiers in Public Health, 2021)
Two COVID-19 outbreaks occurred in residential buildings with overcrowded housing conditions in the city of Göttingen in Germany during May and June 2020, when COVID-19 infection incidences were low across the rest of the country, with a national incidence of 2.6/100,000 population. The outbreaks increased the local incidence in the city of Göttingen to 123.5/100,000 in June 2020. Many of the affected residents were living in precarious conditions and experienced language barriers. The outbreaks were characterized by high case numbers and attack rates among the residents, many asymptomatic cases, a comparatively young population, and substantial outbreak control measures implemented by local authorities. We analysed national and local surveillance data, calculated age- and gender-specific attack rates and performed whole genome sequencing analysis to describe the outbreak and characteristics of the infected population. The authorities’ infection control measures included voluntary and compulsory testing of all residents and mass quarantine. Public health measures, such as the general closure of schools and a public space as well as the prohibition of team sports at local level, were also implemented in the district to limit the outbreaks locally. The outbreaks were under control by the end of June 2020. We describe the measures to contain the outbreaks, the challenges experienced and lessons learned. We discuss how public health measures can be planned and implemented through consideration of the needs and vulnerabilities of affected populations. In order to avoid coercive measures, barrier-free communication, with language translation when needed, and consideration of socio-economic circumstances of affected populations are crucial for controlling infectious disease transmission in an outbreak effectively and in a timely way.